Silica-Coated Mesoporous Carbon as Solid Dessicant in Gas Dehydration Process - Fadlilatul Taufany; Fahmi Fahmi; Nurhamidah Nurhamidah (IPTEK Journal of Proceedings Series, 2015)
Dehydration process using solid desiccant is required to reduce water content to meet pipeline gas GPSA specification (4-7 lb/MMscf). Porous silica gel has a high specific surface area (Grade 12 brand Davisil 800 m2/g), which is generally obtained via a high-cost supercritical technology. This research aims to substitute that of high-cost super critical technology by developing silica-coated mesoporous carbon. This research uses an impregnating-silica method consisting of pretreatment and hydrophilication processes. Here we found that the pretreatment process can increase the surface area of mesoporous carbon from 504.122 m²/g to 823.5 m²/g. While for the hydrophylication process, silica-coated mesoporous carbon was obtained via mechanical and chemical force. Silica-coated mesoporous carbon has adsorption capacity 70.59% of commercial silica gel.